Solvent-Free Lipase-Catalyzed Synthesis of Technical-Grade Sugar Esters and Evaluation of Their Physicochemical and Bioactive Properties - Ran Ye; Douglas Hayes; Rachel Burton; Anjun Liu; Federico Harte; Yuemeng Wang (Catalysts, 2016)
Technical-grade oleic acid esters of sucrose and fructose were prepared using solvent-free biocatalysis at 65 °C, without any downstream purification applied, and their physicochemical and bioactivity-related properties were evaluated and compared to a commercially available sucrose laurate emulsifier. To increase the conversion of sucrose and fructose oleate, prepared previously using solvent-free lipase-catalyzed esterification catalyzed by Rhizomucor miehei lipase (81% and 83% ester, respectively), the enzymatic reaction conditions was continued using CaSO4 to control the reactor’s air headspace and a lipase (from Candida antarctica B) with a hydrophobic immobilization matrix to provide an ultralow water activity, and high-pressure homogenation, to form metastable suspensions of 2.0–3.3 micron sized saccharide particles in liquid-phase reaction media. These measures led to increased ester content of 89% and 96% for reactions involving sucrose and fructose, respectively. The monoester content among the esters decreased from 90% to <70% due to differences in regioselectivity between the lipases. The resultant technical-grade sucrose and fructose lowered the surface tension to <30 mN/m, and possessed excellent emulsification capability and stability over 36 h using hexadecane and dodecane as oils, comparable to that of sucrose laurate and Tween® 80). The technical-grade sugar esters, particularly fructose oleate, more effectively inhibited gram-positive foodborne pathogens (Lactobacillus plantarum, Pediococcus pentosaceus and Bacillus subtilis). Furthermore, all three sugar esters displayed antitumor activity, particularly the two sucrose esters. This study demonstrates the importance of controlling the biocatalysts’ water activity to achieve high conversion, the impact of a lipase’s regioselectivity in dictating product distribution, and the use of solvent-free biocatalysis to important biobased surfactants useful in foods, cosmetics, personal care products, and medicine.